Targeting the DNA damage response in hematological malignancies - De Mel, Sanjay; Lee, Ainsley Ryan; Tan, Joelle Hwee Inn; Tan, Rachel Zi Yi; Poon, Li Mei; Chan, Esther; Lee, Joanne; Chee, Yen Lin; Lakshminarasappa, Satish R.; Jaynes, Patrick William; Jeyasekharan, Anand D. (Frontiers in Oncology, 2024)
Deregulation of the DNA damage response (DDR) plays a critical role in the pathogenesis and progression of many cancers. The dependency of certain cancers on DDR pathways has enabled exploitation of such through synthetically lethal relationships e.g., Poly ADP-Ribose Polymerase (PARP) inhibitors for BRCA deficient ovarian cancers. Though lagging behind that of solid cancers, DDR inhibitors (DDRi) are being clinically developed for haematological cancers. Furthermore, a high proliferative index characterize many such cancers, suggesting a rationale for combinatorial strategies targeting DDR and replicative stress. In this review, we summarize pre-clinical and clinical data on DDR inhibition in haematological malignancies and highlight distinct haematological cancer subtypes with activity of DDR agents as single agents or in combination with chemotherapeutics and targeted agents. We aim to provide a framework to guide the design of future clinical trials involving haematological cancers for this important class of drugs.